The empowerment of health cadres in assisting pregnant women during the covid-19 pandemic - Ana Majdawati; Ivanna Beru Brahmana (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2022)
The questionnaire results on pregnant women at the Primary Health Service of Jetis II in Bantul, Yogyakarta, show that a woman contracts Covid-19. Meanwhile, other findings are that pregnant women get tired quickly (81.82%), many are not orderly to wear masks (76%), about the effects of Covid on mothers and fetuses (over 50%). Health cadres have not been optimal in assisting pregnant women in preventive and follow-up efforts. This community service program aims to empower health cadres in helping pregnant women during the pandemic by increasing knowledge "About Covid-19 for pregnant women, prevention, and management efforts". The service methods are a lecture and brainstorming activity for ten health cadres representing five hamlets. It is hoped that health cadres can become companions for pregnant women during the pandemic, as mediators in delivering health knowledge for mothers and fetuses, and also giving preventive efforts they must. Community service activities through face-to-face and online meetings in Turen Hamlet, Jetis II Community Health Center, and Bantul shows an increasing knowledge of health cadres. The discussion results before the lecture are that 35% of health cadres can answer correctly, and 85% can answer and explain accurately and adequately after the lecture. Conclusion: Efforts to increase knowledge about Covid-19 for pregnant women through health cadres' assistance are necessary to reduce the morbidity and mortality rate of mothers and fetuses.